Carbonate fluorapatite coatings on phillipsite represent a significant sink of phosphorus in abyssal plains of the western Pacific Ocean - Wenxiao Fan; Junming Zhou; Xiaodong Jiang; Huan Zhang; Mei Mi; Peng Yuan; Yanhui Dong; Dong Liu; Yanfu Wei; Jörn Peckmann (Proceedings of the National Academy of Sciences, 2025)
As an essential micronutrient, phosphorus plays a key role in oceanic biogeochemistry, with its cycling intimately connected to the global carbon cycle and climate change. Authigenic carbonate fluorapatite (CFA) has been suggested to represent a significant phosphorus sink in the deep ocean, but its formation mechanisms in oceanic low-productivity settings remain poorly constrained. Applying X-ray absorption near edge structure, transmission electron microscopy, and laser ablation inductively coupled plasma mass spectrometer analyses, we report a unique mineral assemblage where CFA crystals coat phillipsite in abyssal sediments of the East Mariana Basin and the Philippine Sea. This finding suggests that phillipsite provides an ideal microenvironment for CFA formation due to its ability to release calcium cations and its strong adsorption capacity for phosphate anions. The feasibility of such a mechanism was confirmed by long-term (10 mo) laboratory experiments. Furthermore, the CFA forming in the sediment of abyssal plains is found to be enriched in rare earth elements (REE). The previously unrecognized mechanism of CFA formation may therefore not only contribute to the cycling of phosphorus in oceanic low-productivity environments but may also represent a significant sink of REE.